The untold stories of Vietnamese kindergarten teachers: the construction of teacher’s subjectivities in the era of parentocracy - Nguyen, Kim Phuong (My University, 2024)
This thesis examines the construction of kindergarten teachers’ subjectivities under the impact of parentocracy in Vietnamese early childhood education. With the adoption of market mechanisms and the empowerment of parents as consumers, profound changes in the position as well as power among parents, teachers, and schools in education are observed. In Vietnamese education, while the terms “privatization” and “marketization” are avoided in political documents, the reality may reflect an educational landscape of intense competition among schools. There is a robust expansion of private schools and competitive market where parents are given a right to choose school and, potentially navigate children’s learning outcomes as they wish. It is important to note that this market in early childhood education is allowed and encouraged to develop faster compared to the other educational levels. Since the marketization was not explicitly mentioned in policies, there is an open question of whether teachers’ subjectivities are constructed into neoliberal images and how this construction takes place. Therefore, the main aim of this research is an investigation in the above topic which has not been examined in the Vietnamese context. By collecting empirical data, this thesis reveals the marketization in Vietnamese early childhood education and its impact on kindergarten teachers. To achieve the research aim, the thesis is designed to scrutinize into teachers’ perceptions of parents at the current time. This leads to further investigation in teachers’ subjectivities and the difference between two generations of teachers. With the scrutiny of the imbalance of power between teacher and parent under the market mechanism, teachers’ subjectivities are investigated through their perceptions of parents’ role as well as daily practices to interact with children’s main caregiver. The work of Ball (2003) about teachers’ subjectivities is adopted to examine and identify the current subjectivities in early childhood professionals under the pressures of market, competition, and performativity. Through qualitative research involving semi-structured interviews with twelve kindergarten teachers in Hanoi, the complexities of teachers’ constitution in their subjectivities are analyzed with the reflexive thematic analysis. Findings reveal that teachers perceive parents’ role as consumers, demanding caregivers, and also inspectors of teachers’ performance. Furthermore, there is a shift in teachers’ perception of their own role as service providers instead of professionals. The power of the parents is utilized to allow them to intervene in children’s education and teachers’ practices through a system of judgments. Kindergarten teachers perceive this change as a social demand that require their adaptation with a new educational context. Through examination, the construction of teacher’s subjectivities is revealed. There are differences between two generations of the interviewed teachers. While the older generation of teachers is experiencing internal struggles, the younger generation of teachers has gradually internalized the new neoliberal subjectivities who pursue their self-interest. The study reflects a phenomenon that the Vietnamese early childhood education is an example of the expansion of parentocracy in the lower grades of primary education. More importantly, this ideology could lead to the construction of teachers’ subjectivity through the empowerment of parents as consumers and the imbalanced power between parents and teachers. Although different generations respond differently, teachers perceive these transformations as a request from social demands that potentially put them in an irresistible position to change. This construction of teachers’ subjectivities is not a personal responsibility but also a governmental responsibility. There is still an open question about whether the dominance of parentocracy with the support from neoliberalism is making Vietnamese early childhood teachers unconsciously contribute to the inequality among Vietnamese children from the early stages of life. This question is worth examining and reconsidering by teachers’ self-examination of the images of teacher that they are required to turn into. Furthermore, this re-examination is also needed for the Vietnamese ministerial level to ensure the equality among Vietnamese children to receive the education with equal quality.
Keywords: parentocracy, teachers’ subjectivity, Vietnam, early childhood education